Pediatric infections in the first year of life following maternal biologic exposure for autoimmune disorder treatment: A systematic review - Renee Gabrielle Fajardo; Akash Uddandam; Jessie Cunningham; Cristina Longo; Sonia M. Grandi (Pharmacological Research)
Pregnancy induces immunologic and physiologic changes that can alter disease activity for women with autoimmune disorders (AD), and if exacerbated, may necessitate treatment. Biologics are increasingly prescribed due to their targeted effects, but transplacental transfer to the fetus may increase potential risks to the infant. This review examines the risk of infection and respiratory distress in the first year of life among infants born to women with AD using biologics during pregnancy versus infants exposed to standard therapies. We systematically searched five databases from January 2012 to June 2023. Inclusion was restricted to cohort and case-control studies including infants born to women with rheumatoid arthritis, multiple sclerosis, or systemic lupus erythematosus prescribed a biologic or standard therapy during pregnancy. Quality assessment was performed using the ROBINS-I tool for observational studies. Due to between-study heterogeneity in effect estimates and outcomes, studies were not pooled. Of 2975 identified citations, 10 studies were included. In three studies examining the risk of infant infection, findings were inconsistent largely due to lack of precision (OR range: 0.6–1.4, 95 % CI range: 0.2–2.8). For respiratory distress, two studies reported an increased risk among infants exposed to biologics (HR 1.30, 95 % CI 1.03,1.74 and RR 1.52, 95 % CI 1.06, 2.18) while one did not. Most studies (80 %) had a moderate risk of bias. The findings suggest conflicting results for the risk of infant infection and possible associations with respiratory distress. Given the limited number of studies, additional studies are needed to inform treatment decisions for AD during pregnancy.